SOSIALISASI PENTINGNYA BPSK TERHADAP PERLINDUNGAN HUKUM KONSUMEN DI DESA BUAHAN KAJA, KECAMATAN PAYANGAN, KABUPATEN GIANYAR, PROPINSI BALI - Putra, I.M.W; Widhiyaastuti, I.G.A.D.; Dahana, C.D (Buletin Udayana Mengabdi; Vol 16 No 1 (2017), 2018)
The purpose of this activity is to provide an understanding to the Buahan Kaja Villagers, Payangan, Gianyar, regarding the importance of the existence of BPSK as an effort to the legal protection of consumers. The method used through counseling and continued discussions with Villagers. Some of the problems faced by the participants related to the lack of information and dissemination regarding the legal protection of consumers and BPSK, the problem can be solved with the implementation of the street law so as to improve knowledge to some Villagers on various aspects of the legal protection of consumers, including the existence of BPSK in Bali until the preventive measures and repressive in dispute resolution consumer as a consumer protection in general.